TAF-ID: An international thermodynamic database for nuclear fuels applications. (March 2021) - Guéneau, C.; Dupin, N.; Kjellqvist, L.; Geiger, E.; Kurata, M.; Gossé, S.; Corcoran, E.; Quaini, A.; Hania, R.; Smith, A.L.; Piro, M.H.A.; Besmann, T.; et al.
Abstract: The Thermodynamics of Advanced Fuels – International Database (TAF-ID) was developed using the Calphad method to provide a computational tool to perform thermodynamic calculations on nuclear fuel materials under normal and off-normal conditions. Different kinds of fuels are considered: oxide, metallic, carbide and nitride fuels. Many fission products are introduced as well as structural materials (e.g., zirconium, steel, concrete, SiC) and absorbers (e.g., B4 C), in order to investigate the thermochemistry of irradiated fuels and to predict their chemical interaction with the surrounding materials. The approach to develop the database and the models implemented in the database are described. Examples of models for key chemical systems are presented. Finally, a few examples of application calculations on severe accidents with UO2 fuels, irradiated fuel chemistry of MOX and metallic fuels and metallic fuel/cladding interaction show how this tool can be used. To validate the database, the calculations are compared to the available experimental data. A good agreement is obtained which gives confidence in the maturity degree and quality of the TAF-ID database. The working version is only accessible to the participants of the TAF-ID project (Canada, France, Japan, the Netherlands, Republic of Korea, United Kingdom, USA). A public version is accessible by all the NEA countries. The current version contains models on the Am–Fe, Am–Np, Am-O-Pu, Am–U, Am–Zr, C–O–U-Pu, Cr–U, Np–U, Np–Zr, O–U–Zr, Re–U, Ru–U, Si–U, Ti–U, U-Pu-Zr, U–W systems. It is progressively extended with our published assessments. Information on how to join the project is available on the website: https://www.oecd-nea.org/science/taf-id/ . Highlights : The TAF-ID international thermodynamic database is a computational tool for nuclear fuel applications. Key systems for nuclear fuels are modelled using the Calphad method. Fission product chemistry of irradiated fuels is predicted. Chemical interaction with structural materials can be predicted under normal and severe accident conditions. Coupling with kinetics, phase-field, Fuel Performance Code is being performed.